2019
DOI: 10.1002/sctm.18-0289
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugated Carbon Dots for Delivery of siTnfαto Enhance Chondrogenesis of Mesenchymal Stem Cells by Suppression of Inflammation

Abstract: Although a promising strategy, the mesenchymal stem cell (MSC)‐based therapy of cartilage defects is sometimes accompanied with chronic inflammation during the remodeling status, which may hinder cartilage regeneration. During this process, the inflammatory cytokine tumor necrosis factor α (TNFα) plays an important role and may be a potential target. In this study, we investigated the effect of Tnfα RNA interference by introducing a functional and highly safe carbon dot (CD)‐SMCC nanovec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…It is worth to mention that the ability of C‐dots to promote cell osteodifferentiation seems to rise from the unique properties (i.e., size, structure, and surface functionalities) of C‐dots obtained during their preparation, since precursors used for the synthesis of C‐dots demonstrated negligible effects on the cellular osteogenic differentiation . Interestingly, C‐dots have been utilized as a traceable (through their PL) gene delivery nanocarrier for the delivery of model gene (plasmid SOX9), or silenced gene (siTnfα, Figure A) to promote chondrogenesis of MSCs to enhance cartilage repair. Very recently, it has also been reported that C‐dots‐doped calcium phosphate nanorod, without any extraneous gene or inducers, could induce ectopic chondrogenesis, instead of osteogenesis, via the activation of the HIF‐α/SOX‐9 pathway (Figure 17B).…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to mention that the ability of C‐dots to promote cell osteodifferentiation seems to rise from the unique properties (i.e., size, structure, and surface functionalities) of C‐dots obtained during their preparation, since precursors used for the synthesis of C‐dots demonstrated negligible effects on the cellular osteogenic differentiation . Interestingly, C‐dots have been utilized as a traceable (through their PL) gene delivery nanocarrier for the delivery of model gene (plasmid SOX9), or silenced gene (siTnfα, Figure A) to promote chondrogenesis of MSCs to enhance cartilage repair. Very recently, it has also been reported that C‐dots‐doped calcium phosphate nanorod, without any extraneous gene or inducers, could induce ectopic chondrogenesis, instead of osteogenesis, via the activation of the HIF‐α/SOX‐9 pathway (Figure 17B).…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…A) Schematic illustration of the formation of C‐dots‐silenced TNFα complexes and the C‐dots‐based nanocarrier for gene delivery and real‐time monitoring of cellular trafficking in vitro and in vivo for enhancing cartilage repair. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…Fibrinogen and apolipoproteins (AI, AIV, and CIII) bound to CNTs with higher affinity (Bianco et al, 2005). Carbon dots-Sulfosuccinimidyl-4-(N-maleimidomethyl) cyclohexane-1carboxylate were synthesized by crosslinking method (Liu et al, 2019). This complex successfully bound and delivered small interfering RNA.…”
Section: Cbns For Peptide Deliverymentioning
confidence: 99%
“…[100,101] In this context, positively charged CDs were explored as carriers of a remodeling status small interfering RNA (siRNA), namely siTNF-, for the treatment of cartilage defects. [102] The transfection efficiency of the CD-siTNFcomplex in MSCs was higher than using the conventional commercial transfecting agent PEI as carrier, resulting in a higher gene silencing efficiency. The higher transfection efficiency of the CD-siRNA could stem from the small size of the CDs (4-10 nm) and the aggregation effects upon complexation with the siRNA that could prevent enzymolysis.…”
Section: In Vivo Studiesmentioning
confidence: 96%